The early enteral feeding in postoperative period and its influence on recovery of children under the age of 1 year after cardiac surgery - E. Yakimishen; S. Boyko; S. Khemio Arnes; L. Moshkivska; Y. Truba; V. Lazoryshynetz (Ukrainian Journal of Cardiovascular Surgery, 2017)
Aim: determination of postoperative period progress in patients under the age of 1 year after cardiac surgery depending of the time of beginning of enteral feeding.Methods: retrospective analysis of two groups of patients under the age of 1 year which received enteral feeding during the first 24 hours (1st group) and during the first 6 hours (2nd group) after cardiac surgery. Evaluation criteria were: biochemical indicators, postoperative progress and the time of stay in ICU.Results: as a result of the study significant catabolic changes in the 1st group of patients (with late start of enteral feeding) were identified. The postoperative period progress was more favorable, the time of stay in ICU was shorter in the 2nd group.Conclusion: Early enteral feeding decreases the risk of development of postoperative respiratory complications, the frequency of antibacterial therapy changes, the albumin administration and reduces the activation time after cardiac surgery with cardiopulmonary bypass.